2020
DOI: 10.1186/s13045-020-01011-z
|View full text |Cite
|
Sign up to set email alerts
|

New agents and regimens for diffuse large B cell lymphoma

Abstract: As a widely recognized standard regimen, R-CHOP (rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone) is able to cure two-thirds patients with diffuse large B cell lymphoma (DLBCL), and the remaining patients suffer from refractory or relapsed disease due to resistance to R-CHOP and fare poorly. Unsatisfied outcomes for those relapsed/refractory patients prompted efforts to discover new treatment approaches for DLBCL, including chimeric antigen receptor T cells, bispecific T cell engagers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 142 publications
(168 reference statements)
1
67
0
Order By: Relevance
“…In full agreement, our results show that anti-insulin antibody responses are induced by polyvalent insulin complexes generated by chemical crosslinking via disulfide bonds and independent of any additional adjuvants. Sulfhydryl group-containing drugs are used as immunosuppressive medication (Azathioprine (Baranzini, 2013)), antilymphoma treatment (Alethine (Wang et al, 2020)) or acute bronchitis treatment (Erdosteine (Cazzola et al, 2010)). Strikingly, their use was reported to result in the development of anti-insulin autoantibodies (Uchigata et al, 1994;Karimi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In full agreement, our results show that anti-insulin antibody responses are induced by polyvalent insulin complexes generated by chemical crosslinking via disulfide bonds and independent of any additional adjuvants. Sulfhydryl group-containing drugs are used as immunosuppressive medication (Azathioprine (Baranzini, 2013)), antilymphoma treatment (Alethine (Wang et al, 2020)) or acute bronchitis treatment (Erdosteine (Cazzola et al, 2010)). Strikingly, their use was reported to result in the development of anti-insulin autoantibodies (Uchigata et al, 1994;Karimi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We found that the expression level of PDL-1 in DLBCL tissue was significantly higher than in normal tissues but significantly lower than in cHL, which may explain why the efficacy of immunotherapy in DLBCL patients is not as good as that in cHL. Meanwhile, DLBCL patients with a higher expression level of PD-L1 seem to show a correlation with an increased resistance to frontline therapy but always related to prolonged PFS if treated with anti-PD-1 antibody (El Hussein et al, 2020;Wang L. et al, 2020). In line with this, cluster B which was associated with worse prognosis showed a higher expression level of CD274/PD-L1 than cluster A.…”
Section: Discussionmentioning
confidence: 70%
“…Recently, advances in immunotherapy, especially checkpoint blockade, have resulted in clinical success in treatment of late-stage cancers [ 26 ]. As for unsatisfactory outcomes for those relapsed and refractory DLBCL patients, it needs more efforts to discover new therapy approaches, such as immunomodulatory drugs, immune checkpoint inhibitors, and so on [ 27 ]. The relationship analysis between CDH23 expression and immune cell infiltration showed that CDH23 had a negatively significant correlation with tumor purity.…”
Section: Discussionmentioning
confidence: 99%